Woman in Patriarchal Culture: Gender Discrimination and Intersectionality Portrayed in Bob Darling by Carolyn Cooke - Ida Rosida; Lestari Rejeki (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2017)
This article examines gender discrimination, and investigates the relation between gender and social class relation experienced by the main female character, Carla, in the short story entitled Bob Darling by Carolyn Cooke. The method used in this study is descriptive qualitative applying the concept of gender discrimination by Mansour Fakih and the concept of intersectionality by Kimberlé Crenshaw about the connection of multiple dimensions, such as gender and class in making discrimination. This study aims to find how the main female character that lives in the patriarchal culture is depicted in the story. Moreover, it is to show how social segregation strengthens the gender discrimination. Gender discrimination is unjust treatments and assumptions against someone, particularly based on a person’s sex that leads to the role that he or she should play in the society. The different role however, leads to the harm and the loss of person’s right in life especially for woman who lives in patriarchal culture. The results show that stereotype, subordination and violence against woman are experienced by the main female character in the society as the effect of gender discrimination. Then, social class as a division of individual classes based on levels of individual’s position in society that can be determined by wealth, education, occupation, and others has a part in gender discrimination. When the woman is on lower class, she has less power and authority so that it makes a stronger discrimination against her. In conclusion, in the patriarchal culture, the discrimination against woman is not only influenced by the gender itself, but also the social class.DOI: 10.15408/insaniyat.v1i2.4345